PENGARUH KONTROL DIRI TERHADAP PERILAKU KONSUMTIF PENGGUNA E-COMMERCE PADA WANITA DEWASA AWAL SAAT PANDEMI COVID-19 - Mumpuni, Hanum Sasmitanisha Ayu; Marissa, Aski (Jurnal Ilmiah Global Education, 2023)
The Covid-19 pandemic has led to changes in people’s lifestyles, including their shopping habits, with many preferring to shop online through e-commerce platforms. Women are said to engage more frequently in online shopping due to their susceptibility to discounts. This can foster consumeristic behavior, especially among young adult women, and one influencing factor is self-control. This research aims to empirically examine the influence of self-control on consumeristic behavior among young adult women who use e-commerce during the Covid-19 pandemic. A quantitative method was used in this study, with purposive sampling technique to select 102 respondents of young adult women who frequently shop through e-commerce. Data was collected using a questionnaire. Hypothesis testing was conducted through simple regression analysis, and the research results showed that the hypothesis was accepted with a significance value of 0.000 (ρ<0.05) and an R square value of 0.356. This indicates a highly significant influence of self-control on consumeristic behavior, where self-control accounts for 35.6%, while the remaining 64.4% is influenced by other factors not included in the study.